1997
DOI: 10.1128/jb.179.3.838-845.1997
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of host iron sources by Corynebacterium diphtheriae: identification of a gene whose product is homologous to eukaryotic heme oxygenases and is required for acquisition of iron from heme and hemoglobin

Abstract: Corynebacterium diphtheriae was examined for the ability to utilize various host compounds as iron sources. C. diphtheriae C7(-) acquired iron from heme, hemoglobin, and transferrin. A siderophore uptake mutant of strain C7 was unable to utilize transferrin but was unaffected in acquisition of iron from heme and hemoglobin, which suggests that C. diphtheriae possesses a novel mechanism for utilizing heme and hemoglobin as iron sources. Mutants of C. diphtheriae and Corynebacterium ulcerans that are defective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
254
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(258 citation statements)
references
References 55 publications
4
254
0
Order By: Relevance
“…In higher plants, algae, and cyanobacteria, HO generates the open tetrapyrroles as lightharvesting pigments (8). HO has also been identified in several pathogenic bacteria, where its role appears to be the essential "mining" of iron from hemes in the host (9,10). Plant and bacterial HOs are soluble and somewhat shorter (ϳ200 residues) (9, 10) than mammalian HO (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In higher plants, algae, and cyanobacteria, HO generates the open tetrapyrroles as lightharvesting pigments (8). HO has also been identified in several pathogenic bacteria, where its role appears to be the essential "mining" of iron from hemes in the host (9,10). Plant and bacterial HOs are soluble and somewhat shorter (ϳ200 residues) (9, 10) than mammalian HO (11).…”
mentioning
confidence: 99%
“…We report herein on the extension of our 1 H NMR investigation to HmuO, the 216-residue soluble bacterial HO from C. diphtheriae (10), using hHO as a homology model (21). Functional (26,27) and spectroscopic (27,28) studies, as well as mutagenesis (29,30), have confirmed the same mechanism and stereospecificity as for mammalian HOs, although the turnover rate is slower (27); the enzyme has been crystallized (31), and the structure of the substrate hemin complex has been refined to 1.4-Å resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HO has been identified in a wide array of organisms, including mammals (1, 2), insects (3,4), and photosynthetic organisms (5,6). Of particular interest, HO is present in many pathogenic bacteria (7)(8)(9)(10), including Neisseria meningitidis (11) and Pseudomonas aeruginosa (12). These pathogenic bacteria have developed sophisticated heme uptake systems that harness the iron from hemecontaining proteins present in the host (13)(14)(15).…”
mentioning
confidence: 99%
“…Siderophores are secreted molecules that bind free iron and then are captured by bacterial surface receptors that deliver iron for transport across the cytoplasmic membrane (4). In addition to retrieving free iron, bacteria also can acquire iron that is bound by various proteins (4,5). Iron acquisition is critical for the establishment of human infections, because several host proteins sequester iron and reduce the concentration of free iron within tissues in an effort to prevent bacterial growth.…”
mentioning
confidence: 99%